Snow crab (Chionoecetes opilio) hemocytes and hepatopancreas transcriptomes: identification, validation, and application of immune-relevant biomarkers of exposure to noise - Hall, Jennifer R.; Lehnert, Sarah J.; Gonzalez, Emmanuel; Hanlon, Jacqueline M.; Kumar, Surendra; Morris, Corey J.; Rise, Matthew L. (Frontiers in Marine Science, 2023)
The snow crab (Chionoecetes opilio) fishery off the east coast of Newfoundland and Labrador, Canada, has been impacted by annual seismic oil and gas surveying in recent decades, and commercial crab harvesters are concerned that it could potentially affect this resource. A laboratory study was performed to investigate the effects of chronic noise exposure on the transcriptomes of snow crab hemocytes and hepatopancreas, which are important in immunity, metabolism and response to environmental stress. Snow crab were held in replicate control or experimental tanks; on alternating days, the experimental tanks were exposed to noise from an underwater speaker which played a recording of a seismic airgun firing every 10 sec in a continuous loop for 22 weeks (chronic noise). RNA sequencing was used to identify candidate noise-responsive molecular biomarkers in both hemocytes and hepatopancreas. The quantified transcripts of individuals (i.e. n=10 from each of the four groups) were compared using DESeq2, identifying over 300 noise-responsive transcripts in each cell/tissue type. Real-time quantitative polymerase chain reaction (qPCR) assays were designed and run for 61 of these transcripts with significant BLASTx hits. One transcript (rgs2) was significantly (p < 0.05) higher expressed in both hemocytes and hepatopancreas in response to noise; five and seven other transcripts were either significant or showed a non-significant trend of differential expression (0.05 < p ≤ 0.1) in hemocytes (e.g. cfb upregulated, sacs and myof downregulated) and hepatopancreas (e.g. gpx3 and atf3 upregulated, sult1c4 downregulated), respectively. To further investigate the performance and utility of these candidate biomarkers in the field, expression levels of 25 selected transcripts were then examined in the hepatopancreas of snow crab that had been subjected to 2D and 3D seismic surveying using both qPCR and multivariate statistical analyses. Overall, few of these biomarkers showed consistent results in field-collected snow crab, highlighting the need to combine lab and field-based studies to fully evaluate the utility of biomarkers. Nonetheless, our study still identified noise-responsive biomarkers in both settings (including stress and immune relevant genes), providing valuable information for understanding the impact of ocean noise on snow crab physiology and health.